Identification of Genetic Signature Associated With Aging in Pulmonary Fibrosis - Lu, Yanjiao; Chen, Jinkun; Wang, Shanshan; Tian, Zhen; Fan, Yan; Wang, Meijia; Zhao, Jianping; Tang, Kun; Xie, Jungang (Frontiers in Medicine, 2021)
Background: Aging is a strong risk factor and an independent prognostic factor for idiopathic pulmonary fibrosis (IPF). In this study, we aimed to conduct a comprehensive analysis based on gene expression profiles for the role of aging in pulmonary fibrosis. Method: Four datasets (GSE21411, GSE24206, GSE47460 and GSE101286) for clinical IPF patients and 1 dataset for bleomycin (BLM) induced pulmonary fibrosis (BIPF) mouse model (GSE123293) were obtained from Gene Expression Omnibus (GEO). According to different age ranges, both IPF patients and BIPF mice were divided into young and aged groups. The differently expressed genes (DEGs) were systemically analyzed using Gene Ontology (GO) functional, Kyoto Encyclopedia of Genes and Genomes (KEGG) and hub genes analysis. Finally, we verified the role of age and core genes associated with age in vivo. Results: Via the expression profile comparisons of aged and young IPF patients, we identified 108 aging-associated DEGs, with 21 upregulated and 88 downregulated. The DEGs were associated with “response to glucocorticoid”, “response to corticosteroid” and “rhythmic process” in GO biological process (BP). For KEGG analysis, the top 3 significantly enriched KEGG pathways of the DEGs included “IL-17 signaling pathway”, “Mineral absorption” and “HIF-1 signaling pathway”. Through the comparisons of aged and young BIPF mice, a total number of 778 aging-associated DEGs were identified, with 453 genes increased and 325 genes decreased. For GO and KEGG analysis, the DEGs were enriched in extracellular matrix (ECM) and collagen metabolism. The common DEGs of IPF patients and BIPF mice were enriched in the BP category including “induction of bacterial agglutination”, “hyaluronan biosynthetic process” and “positive regulation of heterotypic cell-cell adhesion”. We confirmed that aged BIPF mice developed more serious pulmonary fibrosis. Finally, the 4 aging-associated core genes (Slc2a3, Fga, Hp, Thbs1) were verified in vivo. Conclusion: This study provided new insights of the impact aging in pulmonary fibrosis. We also identified 4 aging-associated core genes (Slc2a3, Fga, Hp, Thbs1) related to the development of pulmonary fibrosis.